Solubility, Antioxidation, and Oral Bioavailability Improvement of Mangiferin Microparticles Prepared Using the Supercritical Antisolvent Method - Mengran Liu; Yankun Liu; Yunlong Ge; Zhaoliang Zhong; Zijian Wang; Tong Wu; Xiuhua Zhao; Yuangang Zu (MDPI AG, 2020)
In view of the poor water solubility and low oral bioavailability of mangiferin (MG), in this study, the supercritical antisolvent (SAS) technology was used to prepare mangiferin microparticles (MG MPs) with N,N-dimethylformamide (DMF) as solvent and carbon dioxide as antisolvent, so as to improve its water solubility, antioxidant capacity and oral bioavailability. Four factors affecting the solubility of the MG MPs were investigated by orthogonal design (OAD), including precipitation pressure, precipitation temperature, MG concentration and feeding speed, and the optimal preparation conditions were determined by range and variance analysis (ANOVA). Under the optimal conditions, the spherical MG MPs with an average diameter of 532.8 nm was obtained, and the yield of the powder was about 95.3%. Scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR), X-Ray Diffractometry (XRD), differential scanning calorimetry (DSC), and thermal gravimetric (TG) were used to analyze the characteristics of the MG MPs. The results obtained showed that the chemical structure of the MG did not change before and after supercritical crystallization, but its particle size and crystallinity decreased significantly. The MG MPs had a higher solubility, and was about 4.26, 2.1 and 2.5 times than that of free MG in water, artificial gastric juice (AGJ) and artificial intestinal juice (AIJ), respectively. The dissolution rate of the MG MPs were also obviously higher than that of free MG. Furthermore, the bioavailability of the MG MPs in vivo was about 2.07 times higher than that of the free MG, and its antioxidant capacity was also much higher than that of free MG, which was close to vitamin C.